Implications of Community-Based Management of Marine Reserves in the Philippines for Reef Fish Communities and Biodiversity - Marriott, Sara E.; Cox, Courtney; Amolo, Rizaller C.; Apistar, Dean; Mancao, Roquelito H.; de Mutsert, Kim (Frontiers in Marine Science, 2021)
Overfishing and destructive fishing practices are major threats to marine biodiversity in the Philippines, where over 1.9 million small-scale fishers are supported by these biodiverse marine communities. Nearly 50% of all marine fish capture in the Philippines is from artisanal fisheries, with much of it not reported or under-reported. Marine reserves, where fishing is prohibited have been created in many local government units to help restore and preserve this biodiversity. The success of these marine reserves is still under serious debate with effective management still representing a significant challenge. The lack of a governance system to centrally managed marine reserves has resulted in nongovernmental organizations developing community-based management schemes. Using independent fisheries data from Rare’s Fish Forever program, we applied PERMANOVA, SIMPER and biodiversity index analyses to evaluate the community structure of reef fish in 20 sites within the Philippines. We analyzed the differences in fish assemblage inside and outside of these marine reserves, before and after community-based management had been implemented. We provide evidence that: i) fish community structure changes within marine reserves after community-based management strategies are implemented; and ii) community-based management of marine fisheries resources protects and promotes biodiversity inside, and in some cases, outside marine reserves. Variability across sites suggests that other social or ecological factors may be influencing the ability of marine reserves to fully protect biodiversity and marine resources. Small-scale fishers in the Philippines participate in mixed-catch harvests and depend on biodiversity and reef community structure for their livelihoods. Thus, this work has implications on how community-based management strategies for marine reserves and adjacent waters may be beneficial for the sustainability of small-scale fishers.